2017
DOI: 10.1002/ange.201703979
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Triple‐Layered versus Helical Be6B11 Clusters: Dual Structural Fluxionality and Multifold Aromaticity

Abstract: Tw olow-lying structures are unveiled for the Be 6 B 11 À nanocluster system that are virtually isoenergetic.T he first, triple-layered cluster has aperipheral B 11 ring as central layer, being sandwiched by two Be 3 rings in acoaxial fashion, albeit with no discernible interlayer BeÀBe bonding.T he B 11 ring revolves like aflexible chain even at room temperature,gliding freely around the Be 6 prism. At elevated temperatures (1000 K), the Be 6 core itself also rotates;t hat is,t wo Be 3 rings undergo relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Most recently, some of us, in collaboration with the group of Zhai, reported an unprecedented multifold fluxionality in Be 6 B 11 − . 74 The computations indicate that Be 6 B 11 − exhibits two nearly isoenergetic global minimum-energy structures: a helix-type C 2 -symmetric cluster and a coaxial multiple-layered C 2v -symmetric system (see Figure 12).…”
Section: Three-dimensional With Multifold Fluxionalitymentioning
confidence: 99%
“…Most recently, some of us, in collaboration with the group of Zhai, reported an unprecedented multifold fluxionality in Be 6 B 11 − . 74 The computations indicate that Be 6 B 11 − exhibits two nearly isoenergetic global minimum-energy structures: a helix-type C 2 -symmetric cluster and a coaxial multiple-layered C 2v -symmetric system (see Figure 12).…”
Section: Three-dimensional With Multifold Fluxionalitymentioning
confidence: 99%
“…Moreover, the calculated total energy of the cluster demands a high level of quantum mechanical methodology to produce reliable energies. Despite that, several algorithms coupled with DFT have been employed to search for the lowest energy structures on the potential energy surface of atomic clusters, such as the kick methodology [65][66][67][68][69][70][71][72][73][74][75][76][77] and genetic algorithms [43,[78][79][80][81]. Our computational procedure to elucidate the lowest energy consisted of a hybrid genetic algorithm called GALGOSON [43,47].…”
Section: Theoretical Methods and Computational Detailsmentioning
confidence: 99%
“…Previous investigations indicated that sp hybridization and multiple aromaticity tend to govern the planar shape for small boron clusters. , The π aromaticity of the planar pure boron ring obeys the classical electron counting rule 4 N + 2, whereas polycyclic structures such as B 18 2– , B 19 – , and B 20 2– and related clusters are classified as disk aromatic species. The bowl-shaped boron B 30 cluster is identified as a typical nonconventional structure which has a pentagonal hole and satisfies a motif of B n @B 2 n @B 3 n with n = 5 . Subsequent studies demonstrated that the B 32 , B 35 , B 36 , and, more recently, B 50 clusters are also considered as members of bowl-shaped clusters which contain a hexagonal and heptagonal hole. The tubular motif of the structure in which B m strings are connected together in antiprism fashion, was observed for boron clusters such as B 20 (double ring), B 27 + , and B 42 (both being triple ring). ,, The tubular shape emphasizes the rich perspective of electron distribution of boron clusters as it presents a tubular aromaticity which can be rationalized by the models of electron in cylinder and hollow cylinder. , Interestingly, fullerene-like structures are also identified for boron clusters including the B 40 , B 42 + , B 44 , and B 46 that contain large heptagonal, octagonal, and nonagonal holes. …”
Section: Introductionmentioning
confidence: 99%